2015
DOI: 10.3171/2014.10.jns14290
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of excellent functional outcome in aneurysmal subarachnoid hemorrhage

Abstract: A lthough the incidence of aneurysmal subarachnoid hemorrhage (aSAH) has remained stable over time, case fatality rates have decreased by 17% during the last three decades. 11,18 In parallel with refinements in endovascular and surgical treatment and advances in neurocritical care, there has also been an improvement in functional outcome. 2,16,19,23 There are many studies on factors predictive of poor functional and cognitive outcome after aSAH, 5,6,22,25 but much less information on predictors of excellent ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
74
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 26 publications
10
74
0
6
Order By: Relevance
“…Notably, this observed negative influence was more evident at the 12-than 6-month follow-ups, suggesting a long-lasting negative effect of RBCT that increases with time (Table 3; Figs. 2, 3), as previously documented in other clinical scenarios [19,20]. The higher rates of unfavorable outcomes observed in patients with TBI receiving RBCT might have been the result of the interaction of several factors.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Notably, this observed negative influence was more evident at the 12-than 6-month follow-ups, suggesting a long-lasting negative effect of RBCT that increases with time (Table 3; Figs. 2, 3), as previously documented in other clinical scenarios [19,20]. The higher rates of unfavorable outcomes observed in patients with TBI receiving RBCT might have been the result of the interaction of several factors.…”
Section: Discussionsupporting
confidence: 52%
“…The median [interquartile range] pretransfusion Hb concentration was 82 [60-110] g/L. Transfused patients received a median of 5 [3][4][5][6][7][8] units of packed RBC with a median length of storage of 15 [11][12][13][14][15][16][17][18][19][20] days. Concomitantly with RBCT, 29 (17.6 %) patients received fresh frozen plasma and 27 (16.4 %) received pooled platelets.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, international, national, and longitudinal comparisons of outcomes for patients with SAH treated using different therapeutic modalities should be discussed in light of socioeconomic indicators, acute stroke care capabilities at the specific time, 13,14,26,28,31 and patient-level characteristics such as SAH severity. 27 The present study is the first to compare outcomes for SAH patients treated with clipping and coiling via a mixed-model analysis of a large nationwide discharge database (DPC database) after adjustment for patient-level characteristics including age, sex, level of consciousness (JCS score), CCI score, and hospital-level CSC capabilities (CSC score). 14,15 Our results revealed that patients who had undergone coiling exhibited significantly higher in-hospital mortality (12.4% vs 8.7%) and shorter hospital stays (32.0 vs 37.0 days) than those in patients who had undergone clipping.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis after SAH is determined by the initial insult as translated into clinical scales, such as the Hunt and Hess grade, but also by the occurrence of complications like vasospasm and delayed cerebral ischemia (DCI) [1,[3][4][5]. Besides these well-known factors, the occurrence of early brain injury at the time of haemorrhage is emerging as a leading cause of mortality [2].…”
Section: Background and Purposementioning
confidence: 99%